Design and material optimization of an Orion re-entry aeroshell for higher structural performance. (2022) - Rao, K. Naga Vardhana; Balguri, Praveen Kumar; Govardhan, D; Vamsi, Ch. Krishna; Sravani, Madhurakavi
Abstract: Space exploration and interplanetary missions are achieved using re-entry capsules for both manned and unmanned missions. Re-entry capsules experience a higher amount of pressure and temperatures during re-entry which induces aerodynamic heating further leading to structural deformation due to shear stress [1] . The research aims to investigate the effect of changing the design parameter spherical nose radius [2] of the Orion capsule shell with different materials by doing static structural analysis. Materials considered for analysis are S glass-epoxy, epoxy resin, carbon-epoxy, E glass-epoxy which are composite materials available in the Ansys material library under engineering data sources. Base design and Optimized designs were modeled in solidworks2020 cad software. FEA analysis was carried out in the Ansys workbench. Static structural analysis performed on the designed cad models and total deformation, maximum shear stress, and shear stress along XY, YZ, and XZ directions were plotted for different parameters by using MATLAB, and performances of the structures are evaluated based on the values. At 11 m spherical nose radius with E glass material achieved less total deformation i.e., 0.0021 m.